Chemosensor properties of 7-hydroxycoumarin substituted cyclotriphosphazenes - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2020)
The newly synthesized cyclotriphosphazene cored coumarin chemosensors 5, 6, and 7 were successfully characterized by H-1 NMR, P-31 NMR, and MALDI-TOF mass spectrometry. Additionally, the photophysical and metal sensing properties of the targeted compounds were determined by fluorescence spectroscopy in the presence of various metals (Li+, Na+, K+, Cs+, Mg2+, Ca2+, Ba2+, Cr3+ Mn2+, Fe3+, Co2+, Al3+, Hg+, Cu2+, Zn2+, Ag+, and Cd2+). The fluorescence titration results showed that compounds 5, 6, and 7 could be employed as fluorescent chemosensors for Fe3+ ions with high sensitivity. The complex stoichiometry between final cyclotriphosphazene chemosensors and Fe3+ ions was also determined by Job's plots.
Keywords: Cyclotriphosphazene; coumarin; fluorescent chemosensor; aqueous media; ON FLUORESCENT CHEMOSENSOR; COUMARIN DERIVATIVES; FE3+ IONS; EMISSION; DYES; CYCLOPHOSPHAZENES